1994
DOI: 10.2466/pr0.1994.75.3f.1499
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Acculturation in Mexican-American Women

Abstract: The purpose of this study was to examine the relationship between depression and acculturation in Mexican-American women. For this purpose, two samples of 67 women from social service agencies in Kansas City and 57 college women from South Texas were examined. Pearson product-moment correlations of scores on depression and acculturation suggested a nonsignificant association (-.02) for the South Texas sample, but a low negative significant relationship (-.29) for the Kansas City group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…While there appears to be much evidence regarding the positive link between acculturation and depression, other studies suggest that acculturation can play a protective role in mental health (Constantine et al, 2004;Cordero & Kurz, 2006;Falcon & Tucker, 2000;Gonzalez, et al, 2001;Kaltman, Green, Mete, Shara, & Miranda, 2010;Masten, Penland, & Nayani, 1994;Potochnick & Perreira, 2010). Kaltman and colleagues (2010) examined 64 Latina immigrants involved in a RCT for depression and found that increased years in the United States significantly predicted decreased risk for depression.…”
Section: Acculturation As a Protective Factormentioning
confidence: 99%
“…While there appears to be much evidence regarding the positive link between acculturation and depression, other studies suggest that acculturation can play a protective role in mental health (Constantine et al, 2004;Cordero & Kurz, 2006;Falcon & Tucker, 2000;Gonzalez, et al, 2001;Kaltman, Green, Mete, Shara, & Miranda, 2010;Masten, Penland, & Nayani, 1994;Potochnick & Perreira, 2010). Kaltman and colleagues (2010) examined 64 Latina immigrants involved in a RCT for depression and found that increased years in the United States significantly predicted decreased risk for depression.…”
Section: Acculturation As a Protective Factormentioning
confidence: 99%
“…Many scholars (Ghaffarian, 1998;Masten, Penland & Nayani, 1994;Meleis, Lipson, & Paul, 1992;Torres-Matrullo, 1976) found that the less acculturated, the more psychiatric symptoms immigrants have. They agree that the most desirable goal for immigrants to adopt is that of integrating into the mainstream of their new culture in such a way that the merits of their own cultures of origin are preserved.…”
Section: Koreans In the United States And Chicagomentioning
confidence: 99%
“…One possibility is that more acculturated Latinos may have access to more psychological resources (e.g., social support) that help them to manifest less dependence on smoking, and these factors together may contribute to successful cessation. Alternatively, greater acculturation is associated with fewer depressive symptoms (Black et al, 1998; Gallagher-Thompson et al, 1997; Masten et al, 1994; Torres & Rollock, 2007; Zamanian et al, 1992), English-language speaking pressures, and pressure toward acculturation (Schwartz & Zamboanga, 2008). The lessening of these pressures may lead to less dependence on smoking.…”
Section: 0 Discussionmentioning
confidence: 99%
“…For example, higher acculturation is related to greater family conflict (Moyerman & Forman, 1992) but lower depressive symptomatology (Black, Markides, & Miller, 1998; Gallagher-Thompson, Tazeau, Basilio et al, 1997; Gonzalez, Haan, & Hinton, 2001; Gonzalez & Gonzalez, 2008; Masten, Penland, & Nayani, 1994; Torres & Rollock, 2007; Zamanian, Thackrey, Starrett et al, 1992). To the extent that acculturation influences important social/interpersonal factors that may be sources of stress, dependence on smoking may serve as coping mechanism among Latino smokers.…”
Section: 0 Introductionmentioning
confidence: 99%